Optimisation of the composition of comprehensively modified self-compacting fine-grained concrete mixtures for vibration-free and low-vibration construction technologies (Международный научный журнал «Инженер», 2026)
The article presents the results of research on optimising the composition of complex modified selfcompactingfine-grained concrete mixtures intended for vibration-free and low-vibration constructiontechnologies. The aim of the work was to establish rational component ratios that ensure an optimalbalance between the rheological and strength characteristics of concrete. The parameters considered foroptimisation were compressive strength at 1, 7 and 28 days, flexural strength, average density, and watercementratio. It was found that the use of a complex modifier, including mineral and chemical additives,contributes to a reduction in the water-cement ratio while maintaining the necessary mobility, increasesearly and final strength, and ensures the formation of a dense and homogeneous material structure withoutthe use of vibration compaction. The results obtained can be used in the development of energy-efficienttechnologies for monolithic construction using self-compacting fine-grained concretes.